The Relation Between Worldviews and Intergenerational Altruism in Turkey: An Empirical Approach - Bulut, Mehmet (Journal for the study of religions and ideologies, 2016)
Intergenerational altruism is an important area of research to understand the impact of culture on economic outcomes. We hypothesize based on recent research about intergenerational altruism and tough love model that worldviews, religious beliefs, and people’s confidence about their worldviews affect intergenerational altruistic economic behaviour. We extend the research on the impact of worldviews on intergenerational altruism by focusing on Turkey. In the empirical analysis, we run probit regressions using data from a large national survey. We find that worldviews, religiosity, and confidence of individuals about their worldviews impact on intergenerational altruistic economic behaviour in Turkey.